Post-Release Health Insurance Utilization Among Ex-Prisoners: A Scoping Review - Khaerunnisa, Icha; Andriany, Megah; Dwiantoro, Luky (UI Scholars Hub, 2025)
The lack of health insurance coverage after prison release significantly reduces access to essential healthcare services, hindering the continuity of care during community reintegration. The evidence on studies of health insurance use following prison release is limited. This scoping review aimed to summarize research on health insurance utilization after release from prison. Literature searches were conducted across databases including ScienceDirect, PubMed, and Scopus. Relevant articles were selected through a two-stage screening process. Data were extracted from the included studies and presented in tabular and descriptive formats. The keywords used were